Metric indicators for evaluating educational initiatives in the context of continuous professional development of a teacher - Исабаева, Даража; Сагимбаева, А.Е.; Шекербекова, Ш.Т.; Ошанова, Н.Т.; Sadirbekova, Д. (Pedagogy and Psychology, 2024)
This article is an analysis of metric indicators used to evaluate the educational initiative of a teacher in the context of continuous professional development. Using metric tools, the authors highlight the effectiveness and impact of initiatives on the professional development of teachers, highlighting key parameters within the framework of motivational-value, operational-activity and reflection-evaluation components. The work is designed to provide a systematic approach to measuring and evaluating educational initiatives, contributing to a more accurate understanding of their impact on the development of the educational process and improving the professional competence of teachers. The presented analysis of metric data contributes to the development of effective strategies to support and improve educational initiatives.